2012
DOI: 10.1117/12.910020
|View full text |Cite
|
Sign up to set email alerts
|

Development of anti-HER2 conjugated ICG-loaded polymeric nanoparticles for targeted optical imaging of ovarian cancer

Abstract: Targeted delivery of therapeutic and imaging agents using surface modified nanovectors has been explored immensely in recent years. The growing demand for site-specific and efficient delivery of nanovectors entails stable surface conjugation of targeting moieties. We have developed a polymeric nanocapsule doped with Indocyanine green (ICG) with potential for targeted and deep tissue optical imaging and phototherapy. Our ICG-loaded nanocapsules (ICG-NCs) have potential for covalent coupling of various targeting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 13 publications
(24 reference statements)
0
7
0
Order By: Relevance
“…9 We have also reported the targeted fluorescent imaging of ovarian cancer cells using anti-human EGFR 2 functionalized ICG-NCs. 58 ICG-NCs can potentially be used as a phototherapeutic agent by generating heat in response to laser irradiation. In a previous study, 59 our group investigated the heat-generating capability of ICG-NCs in response to 808 nm laser irradiation and demonstrated the ability of ICG-NC suspensions to produce temperature rises to ≈80°C.…”
mentioning
confidence: 99%
“…9 We have also reported the targeted fluorescent imaging of ovarian cancer cells using anti-human EGFR 2 functionalized ICG-NCs. 58 ICG-NCs can potentially be used as a phototherapeutic agent by generating heat in response to laser irradiation. In a previous study, 59 our group investigated the heat-generating capability of ICG-NCs in response to 808 nm laser irradiation and demonstrated the ability of ICG-NC suspensions to produce temperature rises to ≈80°C.…”
mentioning
confidence: 99%
“…13 The optical characterization of ICG-NCs demonstrated that anti-HER2 functionalization did not compromise near infrared absorption and fluorescence emission of ICG-NCs. 13 …”
Section: Characterization Of Nanoparticlesmentioning
confidence: 99%
“…We have previously reported the synthesis of ICG-NCs and conjugation of anti-HER2 monoclonal antibody to the surface of ICG-NCs using PEG as linker. 11,13 Briefly, we coat the surface of ICG-NCs with single and double aldehyde terminated PEG, right before conjugation of antibody. The PEG coating reduces non-specific protein adsorption to the surface of ICG-NCs and besides the double aldehyde terminated PEG chains are used as linker to covalently conjugate anti-HER2 to ICG-NCs.…”
Section: Fabrication Of Icg-loaded Nanocapsules and Surface Functionamentioning
confidence: 99%
See 2 more Smart Citations